Classicist Architecture and Large Buildings - Utkutuğ, Ziya; Hurol, Yonca (Chamber of Architects Bursa Section, 1991)
This article presents classicist approach to high-rise buildings and compares it with other approaches.
This article presents classicist approach to high-rise buildings and compares it with other approaches.
Keywords: high-rise building, classicism, architecture